2008
DOI: 10.4103/0970-1591.44255
|View full text |Cite
|
Sign up to set email alerts
|

Small cell cancer of the bladder: The Leon-Berard cancer centre experience

Abstract: Background:Small cell bladder carcinoma is an uncommon tumor. In this retrospective study we report our experience dealing with this disease at the Leon-Berard Cancer Centre.Materials and Methods:We retrospectively analyzed various characteristics of small cell bladder carcinoma: patient demographics, histological diagnosis, disease stage, treatment effects and outcome, in 14 non-metastatic small cell bladder carcinoma patients treated at our institution between 1995 and 2006.Results:The mean age at diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 14 publications
(16 reference statements)
2
20
1
Order By: Relevance
“…It would appear that, compared with having pure scc, having a mixed-histology malignancy confers an adverse prognosis (6.4 months vs. 11.2 months, p = 0.02). That finding conflicts with those in other studies, which found that patients have a similar or better prognosis with mixed ub scc than with pure ub scc 8, 15 .…”
Section: Discussioncontrasting
confidence: 57%
“…It would appear that, compared with having pure scc, having a mixed-histology malignancy confers an adverse prognosis (6.4 months vs. 11.2 months, p = 0.02). That finding conflicts with those in other studies, which found that patients have a similar or better prognosis with mixed ub scc than with pure ub scc 8, 15 .…”
Section: Discussioncontrasting
confidence: 57%
“…As in urothelial carcinoma of the bladder (UCB), the mean age is 65 years, with male predominance, and an association with smoking. [20][21][22] Analogous to UCB, presenting symptoms of SCCB are often related to the presence of a bladder mass and include hematuria, 14,15,20,23,24 dysuria, nocturia, frequency, urinary obstructive symptoms and localized abdominal/ pelvic pain. 14,22,23,25 However, the natural history of SCCB is more aggressive and is associated with poorer prognosis than UCB.…”
Section: Epidemiology/presentationmentioning
confidence: 99%
“…14,22,23,25 However, the natural history of SCCB is more aggressive and is associated with poorer prognosis than UCB. Therefore, in most cases, SCCB will be locally advanced or metastatic [20][21][22][23][26][27][28][29] at diagnosis and follow a pattern of metastases similar to UCB. The most common sites of spread are regional and distant lymph nodes, liver and bones.…”
Section: Epidemiology/presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of patients with advanced disease at diagnosis ranges from 32% to 56% in most retrospective analyses 12,19,24 . Early metastatic spread is usually observed in small cell urinary carcinoma explaining the high relapse rate and the short disease free survival 3,4,19,25,26 .…”
Section: Prognostic Factorsmentioning
confidence: 99%